2011
DOI: 10.1111/j.1349-7006.2011.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of neurone glial‐related cell adhesion molecule is an independent predictor of poor prognosis in advanced colorectal cancer

Abstract: A downstream target of the Wnt pathway, neurone glial-related cell adhesion molecule (Nr-CAM) has recently been implicated in human cancer development. However, its role in colorectal cancer (CRC) pathobiology and clinical relevance remains unknown. In this study, we examined the clinical significance of Nr-CAM protein expression in a retrospective series of 428 CRCs using immunohistochemistry and tissue microarrays. Cox proportional hazards regression was used to calculate hazard ratios (HR) of mortality acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Several genes that inhibit β‐catenin/TCF‐mediated signalling, including AXIN2 , SOX2 , and TCF7 , were up‐regulated. Importantly, we found that DSC2 down‐regulated two metastasis‐related genes, NrCAM and MMP‐9 . These findings clearly demonstrate an association of DSC2 with β‐catenin signalling, which can subsequently affect cell mobility and invasiveness.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Several genes that inhibit β‐catenin/TCF‐mediated signalling, including AXIN2 , SOX2 , and TCF7 , were up‐regulated. Importantly, we found that DSC2 down‐regulated two metastasis‐related genes, NrCAM and MMP‐9 . These findings clearly demonstrate an association of DSC2 with β‐catenin signalling, which can subsequently affect cell mobility and invasiveness.…”
Section: Resultssupporting
confidence: 58%
“…The accumulation of free, soluble β‐catenin in the cytoplasm and nuclei occurs during the carcinogenesis of oesophageal squamous epithelia . Importantly, in a Wnt‐targeted gene array analysis, we found that DSC2 suppresses cell invasion by down‐regulating the expression of NrCAM and MMP9, two well‐characterized metastasis‐related molecules .…”
Section: Discussionmentioning
confidence: 82%
“…Among them, NRCAM, the cell surface glycoprotein, has been reported to be significantly associated with nodal and distant metastasis in colon cancer. NRCAM is also an independent marker of poor prognosis among advanced CRC patients 40 . UPK3A, FAM3D, and LCN2, which participate cancer cell metabolisim, were also downregulated in all PDOs after CUL4B ablation.…”
Section: Discussionmentioning
confidence: 99%
“…CHL1 can be down-or upregulated in human cancer genesis [13]. An increased expression of NrCAM has been correlated to metastatic development and tumorigenesis in different human cancers [7,14,15]. Moreover, overexpression of NrCAM elevates cancer cell motility and invasiveness in vitro and has been linked to a poor prognosis in adult patients [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…An increased expression of NrCAM has been correlated to metastatic development and tumorigenesis in different human cancers [7,14,15]. Moreover, overexpression of NrCAM elevates cancer cell motility and invasiveness in vitro and has been linked to a poor prognosis in adult patients [7,14]. Likewise, overexpression of L1 in adults correlates to tumor progression and metastatic dissemination in glioma, melanoma, ovarial and colon carcinomas [12].…”
Section: Introductionmentioning
confidence: 99%